Introduction: Transhumanism. Beyond the body - Salvador Macip (Mètode Science Studies Journal: Annual Review)
Science allows us to understand the world we live in. Centuries of research have helped us learn more about our place in the universe, and we have discovered a perhaps even more fascinating mystery: how the organism we inhabit works and the reasons why it stops doing so. In this field, as in many others, we have gone from just admiring nature’s wonders to being able to control them.